Presence of indigenous people from Mato Grosso on the internet and in the production of media: militancy, sustainability and memory (Comunicação & Inovação, 2015)
This article presents the data survey conducted onthe internet and audiovisual production to identifyprofiles on social networks, blogs, pages and mediaproduced by the indigenous people of MatoGrosso, Brazil, with a brief analysis of the contentand indigenous presence in the internet and inmedia production. This article is part of a researchproject that aims to think the presence of informationand communication technologies in thecontext of the education of the indigenous peopleof Mato Grosso.
Keywords: Indigenous people. Internet. Culture. Technology.